Prediction of seizure recurrence risk following discontinuation of antiepileptic drugs. (12th July 2021) - Contento, Margherita; Bertaccini, Bruno; Biggi, Martina; Magliani, Matteo; Failli, Ylenia; Rosati, Eleonora; Massacesi, Luca; Paganini, Marco
Abstract: Objective: Discontinuation of antiepileptic drugs (AEDs) in seizure‐free patients is an important goal because of possible long‐term side effects and the social stigma burden of epilepsy. The purpose of this work was to assess seizure recurrence risk after suspension of AEDs, to evaluate predictors for recurrence, and to investigate the recovery of seizure control after relapse. In addition, the accuracy of a previously published prediction model of seizure recurrence risk was estimated. Methods: Seizure‐free patients with epilepsy who had discontinued AEDs were retrospectively enrolled. The frequency of seizure relapses after AED withdrawal as well as prognosis after recurrence were assessed and the predictive role of baseline clinical‐demographic variables was evaluated. The aforementioned prediction model was also validated and its accuracy assessed at different seizure‐relapse probability levels. Results: The enrolled patients (n = 133) had been followed for a median of 3 years (range 0.8–33 years) after AED discontinuation; 60 (45%) of them relapsed. Previous febrile seizures in childhood (hazard ratio [HR] 3.927; 95% confidence interval [CI] 1.403–10.988), a seizure‐free period on therapy of less than 2 years (HR 2.313; 95% CI 1.193–4.486), and persistent motor deficits (HR 4.568; 95% CI 1.412–14.772) were the clinical features associated with relapse risk in univariate analysis. Among these variables, only a seizure‐free period on therapy of less than 2 years was associated with seizure recurrence in multivariate analysis (HR 2.365; 95% CI 1.178–4.7444). Pharmacological control of epilepsy was restored in 82.4% of the patients who relapsed. In this population, the aforementioned prediction model showed an unsatisfactory accuracy. Significance: A period of freedom from seizure on therapy of less than 2 years was the main predictor of seizure recurrence. The accuracy of the previously described prediction tool was low in this cohort, thus suggesting its cautious use in real‐world clinical practice.